Estudo da influência da vibração na medição da rugosidade - Dobes, Jefferson (2014)
This study aimed to identify the effect of interference produced by mechanical vibration on the average values of roughness parameters and associated measurement uncertainty by means of an electromechanical model TR200 roughness - Homis. Tests were performed by applying vibration in the direction perpendicular to the probe travel path, for different values of frequency and amplitude. The generating system consisted of an electrodynamics vibration exciter and the acceleration measurement was performed by means of a piezoelectric accelerometer. The work was carried out according to the following steps: i) measurement of roughness parameters (Ra, Rq, Rz and Rt) of three samples in conditions without vibration. For comparison and analysis, the roughness was also measured, non-contact, using an interferometer; ii) pre - testing, which consisted of roughness measurement and vibration simultaneously on an aluminum sample considering a frequency band of 50 Hz to 150 Hz and four levels of acceleration; iii) 3² factorial design, which was defined from the results obtained in the pre-tests, which were measured Ra, Rq, Rz and Rt in three samples, independent variables were the frequency and acceleration, both on three levels, namely 60Hz, 80 Hz and 100 Hz for the frequency, with acceleration from 0,6 m/s², 1.0 m/s² and 1.6m/s². Analysis of variance, was used to verify if the differences between the mean values of roughness parameters evaluated are significant or not. Finally the measurement uncertainty was evaluated using the Monte Carlo method. The procedure has shown that the mechanical vibration produces changes in the mean values of roughness parameters evaluated and the highest values of expanded uncertainty were found for frequencies of 80 Hz and 100 Hz and acceleration of 1.0 m/s².